Project DESMOS: Development and Evaluation of Self-directed Module in Statistics and Probability - Sagge, Roberto Jr.; Espiritu, Evarose E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Learning is weak not because learning is weak. Learning becomes weak because the modules were not prepared to become self-directed. The goal of this design and development project was to create a self-directed statistics and probability instructional module. Data were gathered from teachers, learners, and experts. The data-gathering instruments were Competency Checklist, Students’ and Experts’ Evaluation Checklist, and Reflection Guide. According on teacher perceptions, a survey of the learners' five least-mastered competencies served as the foundation for the development of the module. This module was pilot tested on a group of Grade 11 learners. Learners utilized the module at home and were asked to answer the exercises. Learners took pictures and short videos while they were answering the module. Afterward, learners evaluated the module. In order to assess the module's level of acceptability, experts were requested to complete the Expert's Evaluation Checklist. Thematic analysis, rank, the mean, and standard deviation were all used as data analysis tools. The results show that the following were the five least-mastered competencies: solving problems involving confidence interval of the population mean, solving problems involving regression analysis, solving problems involving sample size determination, solving problems that require population proportion test of hypothesis, and solving problems involving correlation analysis. Additionally, the experts rated the produced module's acceptability as "highly acceptable." While the learners gave the module a "highly acceptable" rating. As a result, the developed module is appropriate for assisting learners in performing the competencies in the area of Statistics and Probability. It is recommended that teachers should use the Self-directed instructional module for whatever mode of learning their school will have.